Analysis of Youth Role in Empowering Community Competence in Sports Field (Study in KONI Asahan Regency) - Hamdani , Rippy; Tarmizi, Hasan Basri; Rujiman (Journal of Environmental and Development Studies, 2020)
This study aims to analyze the Role of Youth in empowering community competencies in the field of sports, Synergy and Coordination between KONI, Regional Governments, and Youth in empowering and increasing community sports competency in Asahan Regency. This study uses a descriptive research method with a qualitative approach. Youth in Asahan Regency (athletes or youth organizations) played an active role in encouraging youth empowerment to be very proactive in carrying out and participating in every activity carried out by KONI Asahan Regency and the Regional Government. Youth and KONI continued to coordinated well to create policies that can encourage the creation of young people in Asahan Regency who have competitive sports skills. But there are still missing links, especially in the aspect of communication between the local government and Youth Organizations in the process of drafting a youth empowerment program in Asahan Regency. The direction of the policy strategy was fostering accomplished athletes turned out to be quite successful, this was evidenced by the achievements of athletes in several domestic, regional and international championships. The policy objectives of the Asahan Regency and KONI in youth empowerment have been able to answer the increase in youth participation in various activities related to sports activities in Asahan Regency.